Non-invasive intravenous coronary angiography using electron beam tomography and multislice computed tomography. Issue 6 (1st June 2003) - Leber, A W; Knez, A; Becker, C; Becker, A; White, C; Thilo, C; Reiser, M; Haberl, R; Steinbeck, G
Abstract : Background: Electron beam computed tomography (EBCT) and multislice computed tomography (MSCT) are both suitable for non-invasive identification of coronary stenoses. Objective: To compare intravenous coronary EBCT angiography (EBCTA) and MSCT angiography (MSCTA) with regard to image quality and diagnostic accuracy. Methods: EBCTA was done using an Imatron C-150 XP scanner in 101 patients following a standard protocol (slice thickness 3 mm, overlap 1 mm, acquisition time 100 ms, prospective ECG trigger). For MSCTA in a different set of 91 patients (using a Siemens Somatom Plus4VZ scanner), the whole volume of the heart was covered in a spiral technique by four simultaneous detector rows. Using retrospective ECG gating, the raw data were reconstructed in (mean (SD)) 215 (12) axial slices acquired in diastole (slice thickness 1.25 mm, overlap 0.5 mm, acquisition time 250 ms/slice). Results: With EBCTA, 76% of predetermined coronary segments in a nine segment model could be assessed with diagnostic image quality, and with MSCTA, 82%. A low contrast to noise ratio with EBCTA, and the presence of motion artefacts with MSCTA were the main reasons for inadequate image quality. Using conventional angiography as the gold standard, 77% of stenoses of > 50% could be identified correctly with EBCTA and 82% with MSCTA. Significant stenoses were correctly ruled out in 93% of segments with EBCTA, and in 96% of segments with MSCTA. The average contrast to noise ratio was higher with MSCTA than with EBCTA (9.4 v 6.5; p < 0.001). Conclusions: EBCTA and MSCTA show similarly high levels of accuracy for determining and ruling out significant coronary artery stenoses. MSCTA is capable of providing good image quality in more coronary segments than EBCTA because of its better contrast to noise ratio and higher spatial resolution. Motion artefacts seen at heart rates of > 75 beats/min and a higher radiation exposure are the main limitations of MSCTA.